Last day - Rice, Luanne (Thomas & Mercer, 2020)
Years ago, Beth Lathrop and her sister Kate suffered what they thought would be the worst tragedy of their lives the night both the famous painting Moonlight and their mother were taken. The detective assigned to the case, Conor Reid, swore to protect the sisters from then on. Beth moved on, throwing herself fully into the art world, running the family gallery, and raising a beautiful daughter with her husband Pete. Kate, instead, retreated into herself and took to the skies as a pilot, always on the run. When Beth is found strangled in her home, and Moonlight goes missing again, Detective Reid can<U+2019>t help but feel a sense of déjà vu. Reid immediately suspects Beth<U+2019>s husband, whose affair is a poorly kept secret. He has an airtight alibi<U+2014>but he also has a motive, and the evidence seems to point to him. Kate and Reid, along with the sisters<U+2019> closest childhood friends, struggle to make sense of Beth<U+2019>s death, but they only find more questions: Who else would have wanted Beth dead? What<U+2019>s the significance of Moonlight? Twenty years ago, Reid vowed to protect Beth and Kate<U+2014>and he<U+2019>s failed. Now solving the case is turning into an obsession . . .